(untitled) (Hoboken, N.J., 2008)
Introduction to Proteomics is written by seasoned researchers with years of practical experience. In addition to comprehensive discussions of the basic concepts, techniques, and applications of the subject, the text also includes an extensive glossary and a chapter containing laboratory exercises and protocols. While mass spectrometry is central to proteomics, the book discusses all of the analytical techniques a student is likely to need when faced with real–world problems, such as sample preparation, chromatographic and electrophoretic separation, micro–total analysis systems, and bioinformatics.
Keywords: Proteomics,Nghiên cứu protein